The new antlion genus Dominikon gen. nov. with the description of a new species, Dominikon aspoecki sp. nov. (Neuroptera: Myrmeleontidae) - Krivokhatsky, Victor; Dobosz, Roland; Ábrahám, Levente (Zootaxa, 2022)
The genus Dominikon Dobosz, Krivokhatsky & Ábrahám gen. nov. is separated from the genus Nedroledon Navás, 1914, along with two previously described species: Dominikon lagopus (Gerstaecker, 1894) and Dominikon iranensis (Hölzel, 1972) comb. nov. A new species, Dominikon aspoecki Dobosz, Ábrahám & Krivokhatsky sp. nov. is described from Iran and Turkmenistan. The new genus is characterized by the presence of a prominent postventral processus of the ectoproct. The genus Nedroledon includes two valid Western Palaearctic species (Nedroledon anatolicus Navás, 1914 and N. maculatus Zakharenko, 1990). The paper contains a key for both genera, Nedroledon and Dominikon, and a key for the species of the new genus Dominikon. The taxonomic features and habitus of each species are illustrated. New data on the distribution of species of the two related genera Dominikon gen. nov. and Nedroledon Navás, 1914 are also given.